What is intergovernmental about the EU's '(new) intergovernmentalist' turn? Evidence from the Eurozone and asylum crises. Issue 4 (7th June 2021) - Smeets, Sandrino; Zaun, Natascha
Abstract: Engaging with recent claims of increased intergovernmental dynamics, this article asks what exactly is intergovernmental about the EU's major crisis-induced reforms. Drawing on central claims of both New Intergovernmentalism and Liberal Intergovernmentalism, it is demonstrated that the Eurozone reform and the asylum reform differ significantly regarding the role played by the European Council (NI) and the role of institutional expertise provided by supranational actors (LI). While the European Council played a central facilitating role in the Eurozone crisis and worked effectively with the Commission, which provided important technical expertise, expertise in the area of asylum still largely lies with the member states. The Commission therefore acted as a political stakeholder, thus estranging the European Council that subsequently acted as a reform blocker. This article is a first attempt to assess empirically the micro-level foundations of different types of intergovernmentalism and to nuance claims on the weakened role of supranational institutions.